The relationship between physical activity engagement and internet addiction among students in rural academia - Esto, Jomar; Nadela, Lara Ivanah C.; Calixtro, Marichu; Janito, Cheeze R.; Gaspar, Evangeline; Tagare, Jr., Ruben L.; Gulanes, Argin A.; Dee, Michelle R.; Sumambot, Japy O.; Boyles, Pink Floyd M.; Acera, Erika; Pregunta, William R.; Rivas, Jan Lincon C. (Institute of Advanced Engineering and Science, 2025)
This study explores the relationship between physical activity engagement and internet addiction among university students in a rural Philippine academic setting—an understudied context where digital reliance and limited physical access converge. Employing a rigorous quantitative approach through a descriptive-correlational design, the study involved 892 respondents selected via simple random sampling from a premier state university. Data were gathered using the culturally adaptable international physical activity questionnaire (IPAQ) and the internet addiction test (InAT), both established and reliable tools for assessing physical activity levels and problematic internet use. Descriptive and inferential statistics, including Pearson correlation coefficient, were utilized to analyze patterns and relationships within the data. The results indicate a significant negative correlation between physical activity engagement and internet addiction, suggesting that higher physical activity is associated with lower levels of problematic internet use. This finding underscores the protective role of physical activity against digital overdependence and highlights the need to contextualize behavioral health strategies within rural academic environments. The study offers valuable insights for policymakers, educators, and researchers aiming to support student well-being through integrative health and technology-use frameworks.